Identidade e hibridismo cultural na amazônia brasileira: um estudo comparativo de dois irmãos e cinzas do norte, de Milton Hatoum, e a selva, de Ferreira de Castro - Oliveira, Tássia Tavares de (2017)
The present research focuses on the production of the Brazilian contemporary poet Marina Colasanti, having as our literary corpus four of her books of poems (1993), (1998), (2005) and (2009). In general terms, we defend that female poetic production has been for centuries parcially silenced by patriarchal cultural tradition, what justifies our proposal of developing a research in dialogue with established criticism on the literary production by women in the national context from a persective attuned with the field of women and literature. This sounds to us as a still necessary debate, despite considerable advances taken by women writers more recently. We believe that the lyric I in the selected poems by Colasanti gives evidence of relations and tensions established in the cultural field, marked by a gender system that gives priority to the masculine, here questioned by women’s perspective. Thus, we have taken the body as our category of analysis, in order to deal with the selected poems, having feminist and cultural studies as our main theoretical basis, discussing the body as always gendered, never neutral. So, we analyze how representations of the body and eroticism are connected to the feminine, observing the construction of cultural identities in respect to sexual difference. Our methodoly consists of developing a discussion of some gender theories, women’s literary production as well as studies on the history of the body and eroticism, followed by an analytical reading of the selected poems. Colasanti`s poetry is here taken as a way of rupture, of breaking with the historical interdiction imposed to women and the taboos affecting women’s bodies. We conclude that here the lyric eye gives opportunity to women to express or deal with female craving for freedom in respect to their bodies and their lives in wider terms.